Edukasi dan Pemeriksaan Kesehatan Gigi dan Mulut Di Sekolah Menengah Pertama Negeri 30 Makassar - Nurhaedah, Nurhaedah; Anurogo, Dito; Prastyo, Eko; Sari, Ernita; Prehananto, Herlambang; Aripa, Lusyana (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2024)
The dental and oral health care program takes the form of dental health care carried out directly and in a planned manner by Indonesian Dental and Oral Therapists (TGMI) either individually or in groups. This community service activity was carried out with the aim of empowering female students to increase their knowledge and skills regarding the correct way to brush their teeth using a tongue scraper. The method of this PkM (Community Service) activity is Education and Dental and Oral Health Examination for students at Makassar 30 State Junior High School and distributing questionnaires to students. As a result of the activity evaluation, there has been an increase in students' knowledge and skills after education and demonstrations regarding how to maintain dental health by brushing their teeth and using a tongue scraper correctly. Students who have good knowledge about how to maintain dental and oral health have increased and the number of students who are able to brush their teeth properly has increased and students are able to use a tongue scraper correctly too. Therefore, extension activities need to be held periodically to get optimal results.